Mobilidade urbana e hábitos de compra: efeitos na distribuição e na logística para o varejo - Kenyth Alves de Freitas (2015)
The intensification of the urbanization process in developing countries produces large cities with serious planning deficiencies. Consequently, these deficiencies lead to difficulties in mobility of people and products, in turn, give rise to pressures on the most diverse population habits, resulting in distortions of the retail sector configuration. This study set out to analyze the shopping places transfer phenomenon of some products of household consumption basket, interpreting it as an urban mobility problem. For this, we used the database of the Household Budget Survey (POF) of the IBGE, identifying the difference between the choices of buying local residents among the main Brazilian cities and the interior of the respective states, considering their change over time. Indications were identified showing that the choice of food retailers formats changed over the period, as well as shopping sites chosen for the purchase of toiletries. The clothing items did not show significant changes, suggesting that location and convenience are not decisive attributes that market. The purchase of electronic devices even more concentrated over the period, indicating that scale and competition price are important factors in this sector.